Composite insulator with cooling function and embedded microcapsule hydrophobing agent and preparation method of composite insulator

By using a cooling coating and embedded microcapsule hydrophobic agent in the composite insulator, the aging problem of composite insulators under high temperature, high humidity and ultraviolet radiation is solved, and the effect of surface cooling, delaying aging, enhancing hydrophobic properties and extending service life is achieved.

CN119742130APending Publication Date: 2025-04-01TIANFU YONGXING LAB
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411939104.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

Existing composite insulators age quickly under high temperature, high humidity and ultraviolet radiation, and surface hardening or cracking, resulting in a decrease in mechanical strength and electrical properties. The chemical stability of the hydrophobic coating is insufficient, so it cannot effectively reduce water accumulation and filth adhesion in the long run.

Method used

The composite insulator design with cooling and embedded microcapsule hydrophobic agent is adopted. The surface of the umbrella cover substrate is coated with a high thermal conductivity cooling coating, and the internal microcapsule hydrophobic agent is embedded to form microcapsules through emulsion polymerization or interface polymerization to ensure its stability and sustained release effect in complex environments.

Benefits of technology

Significantly reduce the temperature rise of the surface of the umbrella skirt, delay material aging, enhance surface hydrophobic performance, maintain long-term stability, improve the anti-fouling and comprehensive stability of the insulator, extend the service life, and reduce maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742130A_ABST
    Figure CN119742130A_ABST
Patent Text Reader

Abstract

The invention provides a composite insulator with a cooling function and an embedded microcapsule hydrophobing agent and a preparation method of the composite insulator, and relates to the technical field of electric insulating materials. The composite insulator comprises an umbrella cover base material, the surface of the umbrella cover base material is provided with a cooling coating, and a microcapsule water repellent agent is embedded in the umbrella cover base material. The umbrella cover base material is silicone rubber or modified epoxy resin; the cooling coating is prepared from Al2O3 (at) TiO2 / PDA-BN, fluorocarbon resin, isopropanol, a dispersing agent and a flatting agent; the microcapsule water repellent agent is composed of a core layer and a shell layer, the core layer is made of fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is made of polymer resin. The composite insulator has cooling and hydrophobic functions, the two functions are synergistic, the weather resistance of the insulator can be remarkably improved, the service life of the insulator in a severe environment is prolonged, and the defects that in the prior art, materials are fast in aging, poor in hydrophobic durability, single in function and the like are overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electric power insulation materials, and in particular to a composite insulator with a cooling function and an embedded microcapsule hydrophobic agent and a preparation method thereof. Background Art

[0002] With the rapid development of the power system, the safety and reliability of high-voltage transmission lines, as the core equipment for power transmission, are of vital importance. Composite insulators have gradually replaced traditional porcelain and glass insulators with their excellent electrical performance, mechanical strength and lightweight structure, becoming an indispensable key component in transmission lines. However, composite insulators are exposed to complex and changeable outdoor environments such as high temperature and high humidity for a long time, which leads to material aging, performance degradation and increased failure risks, seriously affecting the stability and economy of power grid operation. Therefore, how to improve the weather resistance of composite insulators, delay aging and enhance surface functionality has become a research focus and technical difficulty in the field of insulators.

[0003] The existing technical designs of composite insulators are mostly centered around the modification of shed materials and the application of surface coatings, but these technical means show certain limitations in complex environments. On the one hand, the shed material is exposed to high temperature, high humidity and ultraviolet radiation for a long time, and its aging rate is significantly accelerated, resulting in surface hardening and even cracking, which reduces the mechanical strength and significantly weakens the electrical properties of the surface. On the other hand, the commonly used vulcanized silicone rubber (RTV) coating technology gradually decreases in the long-term operation due to the hydrophobicity of the coating. Especially in high temperature, high humidity or polluted environments, the insufficient chemical stability of the coating will cause the hydrophobicity to decrease rapidly, and it is impossible to continuously and effectively reduce water accumulation and dirt adhesion.

[0004] In addition, existing insulator technologies are usually optimized for a single performance, such as improving hydrophobicity through coatings or improving anti-aging ability through material formula modification, and lack multifunctional collaborative design. In particular, the key issue of surface temperature rise of the shed skirt has not received sufficient attention. Heat accumulation not only accelerates material degradation, but may also cause performance degradation of the hydrophobic coating, further increasing the risk of flashover. Therefore, existing technologies cannot provide comprehensive and reliable solutions in complex environments, and a technical solution that can achieve collaborative optimization between cooling, hydrophobicity and aging resistance is urgently needed. Summary of the invention

[0005] The purpose of the present invention is to provide a composite insulator with cooling and embedded microcapsule hydrophobic agent, which has cooling and hydrophobic functions. The two functions work synergistically, which can not only significantly improve the weather resistance of the insulator, but also extend its service life in harsh environments, overcoming the defects of the prior art such as rapid material aging, poor hydrophobic durability and single function.

[0006] Another object of the present invention is to provide a method for preparing a composite insulator with cooling and embedded microcapsule hydrophobic agent, which can improve the long-term operating stability of the insulator in a high temperature, high humidity and polluted environment.

[0007] The present invention is achieved through the following technical solutions:

[0008] A composite insulator with cooling and embedded microcapsule hydrophobic agent, comprising an umbrella base material, a cooling coating on the surface of the umbrella base material, and a microcapsule hydrophobic agent embedded inside the umbrella base material; the umbrella base material is silicone rubber or modified epoxy resin; the cooling coating comprises Al 2 O 3 @TiO 2 / PDA-BN10-20 parts, fluorocarbon resin60-80 parts, isopropyl alcohol0.1-1 parts, dispersant1-2 parts and leveling agent0.1-0.5 parts; the microcapsule hydrophobic agent consists of a core layer and a shell layer, the core layer is fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is a polymer resin.

[0009] A method for preparing a composite insulator with cooling and embedded microcapsule hydrophobic agent, comprising the following steps:

[0010] S1. Using silicone rubber or modified epoxy resin to prepare the umbrella cover substrate;

[0011] S2, using emulsion polymerization or interfacial polymerization to encapsulate fluorinated modified polystyrene / nano-silica microspheres in a polymer resin to form a microcapsule hydrophobic agent;

[0012] S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, and molding to obtain an insulator umbrella cover;

[0013] S4. Coating a cooling coating on the surface of the insulator cover, curing, and assembling to obtain a composite insulator.

[0014] By coating titanium dioxide with alumina, the dispersion of titanium dioxide and alumina in the coating can be improved, and the photocatalytic performance of titanium dioxide can be reduced while maintaining its excellent ultraviolet shielding performance. The cooling effect of the coating can be improved through the dual effects of ultraviolet shielding and heat conduction. 2 O 3 @TiO 2 Modification of PDA-BN can form multi-path heat conduction channels. 2 O 3 @TiO 2 / PDA-BN particles can present a uniform and compact shape on the surface of the coating. The particles approach each other until they contact each other, and finally form interlaced and connected heat conduction paths in the coating, obtaining a three-dimensional heat conduction network, which improves the thermal conductivity of the coating as a whole and improves the heat dissipation and cooling function of the coating; it can show an active corrosion inhibition effect and improve the long-term anti-corrosion effect of the coating; it can be cross-linked with fluorocarbon resin to form a multi-level structure coating, improving the impact resistance and cooling performance of the coating.

[0015] Titanium dioxide provides cooling performance, mainly responsible for reflecting ultraviolet and infrared rays, reducing surface temperature rise; aluminum oxide improves the mechanical strength and wear resistance of the coating, while enhancing thermal conductivity; boron nitride further improves the thermal conductivity of the coating and reduces surface thermal resistance; fluorocarbon resin further improves the thermal conductivity of the coating and reduces surface thermal resistance. Titanium dioxide itself has strong photochemical activity, and is prone to deactivation, yellowing, and powdering under sunlight, especially ultraviolet rays. Alumina is used to form a uniform and dense film on the surface of titanium dioxide, and the coated aluminum oxide exists in the form of aluminum oxide boehmite and amorphous hydrosol. The formation of a flocculent or fibrous hydrated alumina coating on the surface of titanium dioxide hinders the collision and agglomeration of titanium dioxide particles, and maintains the spatial stability of titanium dioxide particles in the coating; the formation of continuous flocculent hydrated alumina on the surface of titanium dioxide particles significantly increases the hydroxyl content on the surface of the particles, increases the wettability of the particle surface, and accelerates its dispersion in the coating; the formation of a connected flocculent coating increases the zata potential on the surface of titanium dioxide particles, enhances the electrostatic repulsion between particles, hinders the agglomeration of particles, and can significantly improve the dispersibility of titanium dioxide. At the same time, it can also reduce the photocatalytic properties of titanium dioxide without affecting the ultraviolet shielding performance of titanium dioxide, thereby ensuring the cooling performance and anti-aging performance of the cooling coating.

[0016] The coating modification overcomes the so-called "lip-lip" interaction between adjacent layers caused by the difference in electronegativity between B and N in hexagonal boron nitride, prevents hexagonal boron nitride from agglomerating, and overcomes the defect that it is difficult to covalently modify hexagonal boron nitride to improve its dispersibility in the coating due to its chemical stability and lack of surface active groups. PDA-BN can enhance the stress load transfer between hexagonal boron nitride and the resin matrix, and improve the mechanical properties and thermal stability of the coating. At the same time, the active groups such as amino and hydroxyl groups of dopamine can also enhance the interfacial bonding between hexagonal boron nitride and epoxy resin, and improve the performance of the insulator. Using Al 2 O 3 @T iO 2PDA-BN is modified to form a three-dimensional thermal conductive network that supports the pore structure of the coating, further weakening the effects of particle agglomeration and pore collapse, forming obvious stacked pores, and significantly improving the cooling, corrosion resistance and impact resistance of the coating. At the same time, it can also fill the void defects caused by coating curing and improve the interface compatibility and stability with the resin matrix.

[0017] By modifying nano-silica with amino and epoxy groups respectively, the agglomeration between silica particles is reduced, and the bridging reaction between the two groups constructs a silica aggregation structure with a larger pore size. Specifically, the silanol formed by the hydrolysis of alkoxy groups on the surface of γ-aminopropyltriethoxysilane and γ-(2,3-epoxypropyloxy)propyltrimethoxysilane undergoes a condensation reaction with the hydroxyl groups on the surface of silica to form Si-O-Si bonds, thereby loading an organic carbon chain containing active functional groups on the surface of silica to obtain amino- and epoxy-modified nano-silica. The amino group will open the epoxy group under alkaline conditions, and the two silicas can be bridged through the addition reaction of active hydrogen. Due to the steric hindrance between the particles, the pore structure of silica can be regulated to give it a macroporous characteristic. Then, the polystyrene powder and nano-silica with a macroporous structure are compounded to form a micro-nano double structure while increasing the drug loading of the microcapsule. A large number of micropores are formed between the micro-nano double structure, which can trap air to form an air cushion to prevent water from penetrating, so that the polystyrene / nano-silica microspheres have good hydrophobicity and can effectively repel large and small water droplets. Fluorination modification of polystyrene / nano-silica microspheres can introduce a large number of fluorine atoms into the surface of nano-silica and polystyrene to improve the hydrophobicity of the microspheres. Fluorinated polystyrene / nano-silica microspheres and polymer resins are formed into microcapsules with controlled release function through emulsion polymerization or interfacial polymerization, which can ensure its stability and sustained release effect in complex environments. After the microcapsule is damaged, the fluorinated polystyrene / nano-silica microspheres are gradually released on the surface of the umbrella cover, which can maintain the long-term hydrophobicity of the insulator.

[0018] The umbrella cover substrate may also include a curing agent, silicon powder, an antioxidant and a dispersant, which can improve the mechanical and electrical properties of the insulator. The curing agent is an epoxy curing agent, the antioxidant is a benzothiophene compound or an aromatic amine compound, and the dispersant is sodium silicate or polyacrylic acid. In the cooling coating, the leveling agent is an acrylate leveling agent, and the dispersant is a polyphosphate dispersant.

[0019] Before coating the cooling coating on the surface of the umbrella cover substrate, the umbrella cover substrate is also cleaned and activated. A surface cleaning and activation process (such as plasma treatment or chemical activation) is used to remove impurities on the umbrella cover surface and increase the surface energy, thereby enhancing the adhesion between the cooling coating and the umbrella cover substrate, ensuring that the coating is stable for a long time and does not peel off, thereby further improving the service life and performance reliability of the coating.

[0020] Furthermore, A l 2 O 3 @T iO 2 The preparation method of / PDA-BN is as follows: titanium dioxide slurry and soluble aluminum salt are mixed and reacted to obtain Al 2 O 3 @T iO 2 ; The hexagonal boron nitride was treated with dopamine hydrochloride to obtain PDA-BN; the Al treated with a silane coupling agent 2 O 3 @T iO 2 Add to the PDA-BN suspension and perform ultrasonic treatment.

[0021] Furthermore, A l 2 O 3 @T iO 2 The mass ratio of PDA-BN is 1:3-4.

[0022] Soluble aluminum salt is added to the titanium dioxide slurry with a pH value of 9-10, treated at 50-80°C for 1-5 hours, and then the pH is adjusted to 10.5-11.5 and aged for 2 hours. The coating amount of aluminum oxide is 1-5% of the mass of titanium dioxide to obtain Al 2 O 3 @T iO 2 . 0.484g Tris was added to 300mL deionized water, and 0.1mol / L dilute hydrochloric acid was slowly added to adjust the pH value to 8.5. 0.8g dopamine hydrochloride was added to the above mixture under constant stirring, and then 2g hexagonal boron nitride powder was quickly added to the mixed solution under rapid stirring. The final mixture was ultrasonically treated for 3h, and balanced at 60℃ for 24h, centrifuged, filtered, washed, solid-liquid separated, and dried to obtain PDA-BN. 0.3g PDA-BN was added to 50mL N,N-dimethylformamide and ultrasonically treated for 1h to form a uniform suspension; 0.2g Al 2 O 3 @T iO 2 and 4 g KH550 were added to 100 g anhydrous ethanol, stirred for 30 min and ultrasonically treated for 3 h, centrifuged and dried to obtain modified A l 2 O 3 @T i O 2; 0.1g modified A l 2 O 3 @T i O 2 Add to the suspension, ultrasonicate for 1h, then stir at 105℃ for 6h, centrifuge, wash, and dry to obtain Al 2 O 3 @T iO 2 / PDA-BN.

[0023] Furthermore, the preparation method of fluorinated modified polystyrene / nano-silica microspheres is as follows: a. using nano-silica to prepare amino-modified silica and epoxy-modified silica; b. mixing the amino-modified silica and epoxy-modified silica to obtain a nano-silica intermediate; c. mixing polystyrene powder, dodecafluoroheptyltrimethoxysilane and the nano-silica intermediate to obtain polystyrene / nano-silica microspheres; d. treating the polystyrene / nano-silica microspheres with a fluorine-containing silane coupling agent.

[0024] Furthermore, the mass ratio of the polystyrene powder, dodecafluoroheptyltrimethoxysilane and the nano-silica intermediate is 1:5-10:1.

[0025] Disperse two equal portions of nano-silica in 75 mL of deionized water, stir evenly, heat to 50°C, mix 0.58 mmol / g γ-aminopropyl triethoxysilane and 0.48 mmol / g γ-(2,3-epoxypropoxy)propyl trimethoxysilane with an equal mass of anhydrous ethanol, add dropwise to the reaction system, keep constant temperature at 50°C for 1 hour, 70°C for 1 hour, and 80°C for 1 hour, respectively, to obtain amino- and epoxy-modified silica emulsions; mix the two emulsions, adjust the pH value to 8-9, keep constant temperature at 65°C for 3 hours, filter, and dry to obtain a nano-silica intermediate with a macroporous structure. Mix polystyrene powder, dodecafluoroheptyl trimethoxysilane and nano-silica intermediate, treat at 95-105°C for 6-8 hours, wash, and obtain polystyrene / nano-silica microspheres. Add polystyrene / nano-silica microspheres to the reaction system of ethanol and fluorine-containing silane coupling agent, stir, ultrasonically treat for 10-20 minutes, and dry to obtain fluorinated modified polystyrene / nano-silica microspheres. The mass ratio of polystyrene / nano-silica microspheres, ethanol and fluorine-containing silane coupling agent is 3-5:30-50:0.5-2.

[0026] Furthermore, the modified epoxy resin is a fluorinated modified epoxy resin.

[0027] Furthermore, the polymer resin is any one of polyacrylate resin, polyurethane resin and epoxy resin.

[0028] The preparation process of the microcapsules is as follows: fluorinated modified polystyrene / nano-silica microspheres and emulsifiers are mixed to obtain an emulsion, polymer resins are mixed with the emulsion, the pH of the mixture is adjusted to 2-5, and the temperature is raised to 50-60°C to allow the polymer resins to cross-link on the surface of the microspheres to form a shell layer. The emulsifier is sodium dodecylbenzene sulfonate or polyvinyl alcohol, and the amount of the emulsifier added is 1.4-3.5% of the mass of the microspheres.

[0029] Furthermore, the particle size of the microcapsule hydrophobic agent is 1-10 μm to ensure uniform distribution and no influence on the mechanical properties of the umbrella cover. The hydrophobic agent is gradually released on the surface of the umbrella cover to maintain the long-term hydrophobic properties of the insulator.

[0030] Furthermore, the mass ratio of the microcapsule hydrophobic agent to the umbrella cover substrate is 0.05-0.15:1. Through compression molding and high-temperature curing technology, it is stably embedded in the surface layer of the umbrella cover substrate, which not only retains the mechanical and insulating properties of the material, but also gives it a hydrophobic function. During the molding process, temperature control technology is used to prevent the microcapsules from being destroyed in a high temperature environment, ensuring that the microcapsule embedding structure forms a stable distribution inside the material, thereby continuously providing surface hydrophobic function during the long-term operation of the insulator.

[0031] The technical solution of the present invention has at least the following advantages and beneficial effects:

[0032] (1) Significantly reduce the temperature rise on the shed surface and delay material aging: By coating the shed surface with a high thermal conductivity cooling coating, the shed surface temperature is reduced by utilizing the UV shielding and thermal conductivity of the cooling coating. At the same time, the three-dimensional thermal conductive network formed in the cooling coating can further accelerate its heat dissipation and cooling effect. This cooling effect effectively reduces the impact of heat accumulation on the aging of the shed base material and extends the service life of the composite insulator.

[0033] (2) Enhance surface hydrophobicity and maintain long-term stability: The microcapsules embedded in the umbrella cover can gradually release hydrophobic agents when the umbrella skirt surface is worn or aged, maintaining the hydrophobicity of the surface, significantly reducing dirt adhesion and water accumulation, providing long-term dynamic hydrophobic protection, and significantly extending the effective time of hydrophobic performance, solving the problem of easy attenuation of hydrophobic performance of traditional surface coatings. The use of macroporous nano-silica and polystyrene powder composites can increase the drug loading of microcapsules and enhance their hydrophobic effect.

[0034] (3) Multifunctional synergy to optimize comprehensive performance: The combination of cooling coating and embedded microcapsule technology achieves functional synergy. The cooling coating reduces the surface temperature rise while protecting the microcapsule structure inside the umbrella cover, delaying the release rate of the hydrophobic agent; the hydrophobic function continuously provided by the microcapsules further reduces the condensation effect of water, indirectly reducing the heat accumulation pressure on the surface, achieving mutual enhancement of the two functions, and significantly improving the anti-pollution flashover performance and comprehensive stability of the insulator.

[0035] (4) Strong weather resistance and adaptability to complex environments: The coating and the umbrella cover base material are made of a highly weather-resistant material system that can resist the long-term effects of ultraviolet rays, humidity and pollution. Even in high temperature, humid and severely polluted environments, the performance of the composite insulator can remain stable, meeting the needs of long-term operation of transmission lines.

[0036] (5) Extend service life and reduce maintenance costs: Combined with cooling and hydrophobic functions, the material aging rate of composite insulators is significantly reduced, and the surface functionality is maintained for a long time, which can effectively reduce maintenance frequency and operation and maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 A process flow chart of a composite insulator with cooling and embedded microcapsule hydrophobic agent provided by the present invention;

[0038] Figure 2 A comparison chart of the cooling performance of the umbrella cover with the cooling coating and the bare umbrella cover provided by the present invention;

[0039] Figure 3 A comparison chart of the hydrophobic performance of an insulator with an embedded microcapsule hydrophobic agent and an insulator sprayed with RTV provided by the present invention. DETAILED DESCRIPTION

[0040] The present invention is further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Unless otherwise specified, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0041] Example 1

[0042] A composite insulator with cooling and embedded microcapsule hydrophobic agent, comprising an umbrella base material, a cooling coating on the surface of the umbrella base material, and a microcapsule hydrophobic agent embedded inside the umbrella base material; the umbrella base material is a fluorinated modified epoxy resin; the cooling coating comprises Al 2 O 3 @TiO 2 / PDA-BN(Al 2 O 3 @T iO 2 and PDA-BN in a mass ratio of 1:3) 10g, fluorocarbon resin 60g, isopropyl alcohol 0.1g, polyphosphate 1g and acrylate leveling agent 0.1g; the microcapsule hydrophobic agent consists of a core layer and a shell layer, the core layer is fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is polyacrylate resin.

[0043] The preparation method comprises the following steps:

[0044] S1, melting the fluorinated modified epoxy resin, and extruding it to obtain an umbrella cover substrate;

[0045] S2, mixing fluorinated modified polystyrene / nano-silica microspheres and sodium dodecylbenzene sulfonate to obtain an emulsion, wherein the amount of sodium dodecylbenzene sulfonate added is 1.4% of the mass of the microspheres, mixing polyacrylate resin and the emulsion, adjusting the pH of the mixture to 2, and heating the mixture to 50° C. to obtain a microcapsule hydrophobic agent, wherein the particle size of the microcapsule hydrophobic agent is 5 μm;

[0046] S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, wherein the mass ratio of the microcapsule hydrophobic agent to the umbrella cover base material is 0.1:1, and performing compression molding to obtain an insulator umbrella cover;

[0047] S4. Coat a cooling coating on the surface of the insulator cover and solidify it. Clean and plasma treat the coated cover, and then assemble it with glass fiber core rods, metal ends and other components into a complete composite insulator.

[0048] Example 2

[0049] A composite insulator with cooling function and embedded microcapsule hydrophobic agent, comprising a cover substrate, a cooling coating on the surface of the cover substrate, and a microcapsule hydrophobic agent embedded inside the cover substrate; the cover substrate is silicone rubber; the cooling coating comprises Al 2 O 3 @TiO 2 / PDA-BN(Al 2 O 3 @TiO 2 and PDA-BN (the mass ratio is 1:3.5) 20g, fluorocarbon resin 80g, isopropyl alcohol 1g, polyphosphate 2g and acrylate leveling agent 0.5g; the microcapsule hydrophobic agent consists of a core layer and a shell layer, the core layer is fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is polyurethane resin.

[0050] The preparation method comprises the following steps:

[0051] S1, melting the fluorinated modified epoxy resin, and extruding it to obtain an umbrella cover substrate;

[0052] S2, mixing fluorinated modified polystyrene / nano-silica microspheres and polyvinyl alcohol to obtain an emulsion, wherein the amount of polyvinyl alcohol added is 2% of the mass of the microspheres, mixing polyurethane resin and the emulsion, adjusting the pH of the mixture to 3, and heating the mixture to 55° C. to obtain a microcapsule hydrophobic agent, wherein the particle size of the microcapsule hydrophobic agent is 10 μm;

[0053] S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, wherein the mass ratio of the microcapsule hydrophobic agent to the umbrella cover base material is 0.15:1, and performing compression molding to obtain an insulator umbrella cover;

[0054] S4. Coat a cooling coating on the surface of the insulator cover and solidify it. Clean and plasma treat the coated cover, and then assemble it with glass fiber core rods, metal ends and other components into a complete composite insulator.

[0055] Example 3

[0056] A composite insulator with cooling and embedded microcapsule hydrophobic agent, comprising an umbrella base material, a cooling coating on the surface of the umbrella base material, and a microcapsule hydrophobic agent embedded inside the umbrella base material; the umbrella base material is a fluorinated modified epoxy resin; the cooling coating comprises Al 2 O 3 @TiO 2 / PDA-BN(Al 2 O 3 @T iO 2 The mass ratio of PDA-BN is 1:4) 15g, fluorocarbon resin 70g, isopropyl alcohol 0.3g, polyphosphate 1.5g and acrylate leveling agent 0.4g; the microcapsule hydrophobic agent consists of a core layer and a shell layer, the core layer is fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is epoxy resin.

[0057] The preparation method comprises the following steps:

[0058] S1, melting the fluorinated modified epoxy resin, and extruding it to obtain an umbrella cover substrate;

[0059] S2, mixing fluorinated modified polystyrene / nano-silica microspheres and sodium dodecylbenzene sulfonate to obtain an emulsion, wherein the amount of sodium dodecylbenzene sulfonate added is 3% of the mass of the microspheres, mixing epoxy resin and the emulsion, adjusting the pH of the mixture to 4, and heating the mixture to 58° C. to obtain a microcapsule hydrophobic agent, wherein the particle size of the microcapsule hydrophobic agent is 1 μm;

[0060] S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, wherein the mass ratio of the microcapsule hydrophobic agent to the umbrella cover base material is 0.05:1, and performing compression molding to obtain an insulator umbrella cover;

[0061] S4. Coat a cooling coating on the surface of the insulator cover and solidify it. Clean and plasma treat the coated cover, and then assemble it with glass fiber core rods, metal ends and other components into a complete composite insulator.

[0062] Example 4

[0063] A composite insulator with cooling function and embedded microcapsule hydrophobic agent, comprising a cover substrate, a cooling coating on the surface of the cover substrate, and a microcapsule hydrophobic agent embedded inside the cover substrate; the cover substrate is silicone rubber; the cooling coating comprises Al 2 O 3 @TiO 2 / PDA-BN(Al 2 O 3 @TiO 2 and PDA-BN in a mass ratio of 1:3.2) 12g, fluorocarbon resin 65g, isopropyl alcohol 0.8g, polyphosphate 1.8g and acrylate leveling agent 0.4g; the microcapsule hydrophobic agent consists of a core layer and a shell layer, the core layer is fluorinated modified polystyrene / nano-silica microspheres, and the shell layer is polyacrylate resin.

[0064] The preparation method comprises the following steps:

[0065] S1, melting the fluorinated modified epoxy resin, and extruding it to obtain an umbrella cover substrate;

[0066] S2, mixing fluorinated modified polystyrene / nano-silica microspheres and polyvinyl alcohol to obtain an emulsion, wherein the amount of polyvinyl alcohol added is 3.5% of the mass of the microspheres, mixing polyacrylate resin and the emulsion, adjusting the pH of the mixture to 5, and heating the mixture to 60° C. to obtain a microcapsule hydrophobic agent, wherein the particle size of the microcapsule hydrophobic agent is 2 μm;

[0067] S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, wherein the mass ratio of the microcapsule hydrophobic agent to the umbrella cover base material is 0.08:1, and performing compression molding to obtain an insulator umbrella cover;

[0068] S4. Coat a cooling coating on the surface of the insulator cover and solidify it. Clean and plasma treat the coated cover, and then assemble it with glass fiber core rods, metal ends and other components into a complete composite insulator.

[0069] Comparative Example 1

[0070] In this comparative example, the mass ratio of the microcapsule hydrophobic agent to the umbrella cover substrate is 0.01:1, and the rest is the same as in Example 1.

[0071] Comparative Example 2

[0072] In this comparative example, the mass ratio of the microcapsule hydrophobic agent to the umbrella cover substrate is 2:1, and the rest is the same as in Example 1.

[0073] Comparative Example 3

[0074] In this comparative example, the particle size of the microcapsule hydrophobic agent is 0.2 μm, and the rest is the same as in Example 1.

[0075] Comparative Example 4

[0076] In this comparative example, the particle size of the microcapsule hydrophobic agent is 15 μm, and the rest is the same as Example 1.

[0077] Comparative Example 5

[0078] In this comparative example, the hexagonal boron nitride in the temperature-cooling coating is not modified, and the rest is the same as in Example 1.

[0079] Comparative Example 6

[0080] In this comparative example, titanium dioxide is not coated in the temperature-cooling coating, and the rest is the same as in Example 1.

[0081] Comparative Example 7

[0082] In this comparative example, Al 2 O 3 @T i O 2 PDA-BN was modified to only have Al 2 O 3 @T iO 2 The other steps are the same as those in Example 1.

[0083] Comparative Example 8

[0084] In this comparative example, the core layer is fluorinated modified nano-silica microspheres, and the rest is the same as in Example 1.

[0085] Comparative Example 9

[0086] In this comparative example, the core layer is fluorinated modified polystyrene microspheres, and the rest is the same as in Example 1.

[0087] Comparative Example 10

[0088] In this comparative example, the nano-silicon dioxide in the core layer is ordinary nano-silicon dioxide, and the rest is the same as in Example 1.

[0089] Test example

[0090] The performance of the cooling coatings of Examples 1-4 and Comparative Examples 5-7 was tested. The thermal conductivity was measured at 25°C using a thermal conductivity analyzer according to the national standard GB / T10294-2008. The cooling temperature difference was measured according to the industry standard JG / T235-2014. The water resistance and alkali resistance were measured according to the national standard GB / T9755-2014. The results are as follows:

[0091] Table 1

[0092] project Thermal conductivity (W / (m·K) Cooling temperature difference (℃) 96h water resistance 48h alkali resistance Example 1 0.175 3.3 No abnormality No abnormality Example 2 0.178 3.1 No abnormality No abnormality Example 3 0.181 3.0 No abnormality No abnormality Example 4 0.179 3.2 No abnormality No abnormality Comparative Example 5 0.148 2.0 No abnormality No abnormality Comparative Example 6 0.153 2.2 No abnormality No abnormality Comparative Example 7 0.161 2.4 No abnormality No abnormality

[0093] It can be seen from Table 1 that the cooling coating of the embodiment of the present invention has a high thermal conductivity, a large cooling temperature difference, and good thermal radiation performance. In addition, the coating is water-resistant and alkali-resistant and has good durability.

[0094] The microcapsule hydrophobic agent of Example 1, Comparative Examples 3-4, and 8-10 was mixed with polyurethane, and acetone was used as a solvent, and ultrasonic dispersion was performed to obtain a uniform suspension, and the suspension was dropwise applied to a glass slide, and allowed to stand at room temperature for 2-3 minutes. The temperature of the glass slide was raised to 40°C for curing for 1 hour, and then raised to 80°C for curing for 2 hours to obtain a hydrophobic coating.

[0095] The contact angle of the coatings prepared above was measured by the sessile drop method. The specific method is: 5 sites were selected for each coating, 2 μL of water was dropped on them, the contact angles were measured, and the average contact angle of each coating was calculated. The measurement results are as follows:

[0096] Table 2

[0097] project Contact angle (°) Coating appearance Example 1 159.35 Coating surface intact Comparative Example 3 149.08 Coating surface intact Comparative Example 4 147.85 Coating surface intact Comparative Example 8 143.42 Coating surface intact Comparative Example 9 142.89 Coating surface intact Comparative Example 10 145.67 Coating surface intact

[0098] It can be seen from Table 2 that the microcapsule hydrophobic agent of the embodiment of the present invention has a larger contact angle and has good hydrophobic performance.

[0099] The hydrophobicity of the insulator covers prepared in Examples 1-4 and Comparative Examples 1-2 was tested according to IEC TS62073:2016 standard, and the results were as follows:

[0100] Table 3

[0101]

[0102]

[0103] According to Table 3, the average hydrophobic angle of the insulator cover of the embodiment of the present invention is larger, the rolling angle is smaller, the hydrophobic recovery time is shorter, and the wetted area is smaller, indicating that the insulator of the present invention has better hydrophobic performance.

[0104] The composite insulator and the bare umbrella cover prepared in Example 1 were subjected to a cooling performance test. The test method was: the composite insulator and the bare umbrella cover were heated for a certain period of time respectively, and the heating rate and the temperature change in the time period were detected.

[0105] like Figure 2 As shown, the test results show that the insulator umbrella cooling material coating of the present invention has an obvious cooling effect.

[0106] The composite insulator prepared in Example 1 and the insulator with RTV sprayed on the surface were tested for hydrophobicity. The test method is: the insulator samples coated with microcapsule hydrophobic agent and the insulator samples sprayed with RTV are placed in an outdoor natural environment respectively, and the changes in the hydrophobicity of the samples are observed through long-term exposure. Samples are collected once a quarter, the contact angle of water droplets on the surface is measured, and the contact angle retention rate is calculated to evaluate the retention effect of the hydrophobicity.

[0107] Where, contact angle retention (%) = θ t / θ 0 ×100%,θ t represents the contact angle value measured at time t, θ 0 represents the initial contact angle value.

[0108] like Figure 3 As shown, the hydrophobic performance (%) is the contact angle retention rate (%). The test results show that the microcapsule hydrophobic agent maintains a high hydrophobic performance in long-term use and has better durability than surface spray RTV.

[0109] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite insulator with cooling function and embedded microcapsule hydrophobic agent, characterized in that: It comprises an umbrella cover substrate, the surface of which is provided with a cooling coating, and a microcapsule hydrophobic agent is embedded in the umbrella cover substrate; the umbrella cover substrate is silicone rubber or modified epoxy resin; The cooling coating comprises, by weight, 5-15 parts of Al2O3@TiO2 / PDA-BN, 60-80 parts of fluorocarbon resin, 0.1-1 parts of isopropanol, 1-2 parts of dispersant and 0.1-0.5 parts of leveling agent; The microcapsule hydrophobic agent consists of a core layer and a shell layer, wherein the core layer is fluorinated modified polystyrene / nano silicon dioxide microspheres, and the shell layer is a polymer resin.

2. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 1, characterized in that: The preparation method of the Al2O3@TiO2 / PDA-BN is as follows: titanium dioxide slurry and soluble aluminum salt are mixed and reacted to obtain Al2O3@TiO2; hexagonal boron nitride is treated with dopamine hydrochloride to obtain PDA-BN; Al2O3@TiO2 treated with a silane coupling agent is added to a suspension of PDA-BN for ultrasonic treatment.

3. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 2, characterized in that: The mass ratio of Al2O3@TiO2 and PDA-BN is 1:3-4.

4. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 1, characterized in that: The preparation method of the fluorinated modified polystyrene / nano-silica microspheres comprises the following steps: a. preparing amino-modified silica and epoxy-modified silica using nano-silica; b. mixing the amino-modified silica and epoxy-modified silica to obtain a nano-silica intermediate; c. mixing polystyrene powder, dodecafluoroheptyltrimethoxysilane and the nano-silica intermediate to obtain polystyrene / nano-silica microspheres; and d. treating the polystyrene / nano-silica microspheres with a fluorine-containing silane coupling agent.

5. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 4, characterized in that: The mass ratio of the polystyrene powder, dodecafluoroheptyltrimethoxysilane and the nano-silicon dioxide intermediate is 1:5-10:

1.

6. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to any one of claims 1 to 5, characterized in that: The modified epoxy resin is a fluorinated modified epoxy resin.

7. The composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 6, characterized in that: The polymer resin is any one of polyacrylate resin, polyurethane resin and epoxy resin.

8. The method for preparing a composite insulator with cooling and embedded microcapsule hydrophobic agent according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Using silicone rubber or modified epoxy resin to prepare the umbrella cover substrate; S2, using emulsion polymerization or interfacial polymerization to encapsulate fluorinated modified polystyrene / nano-silica microspheres in a polymer resin to form a microcapsule hydrophobic agent; S3, blending the microcapsule hydrophobic agent and the umbrella cover base material, and molding to obtain an insulator umbrella cover; S4. Coating a cooling coating on the surface of the insulator cover, curing, and assembling to obtain a composite insulator.

9. The method for preparing a composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 8, characterized in that: The particle size of the microcapsule hydrophobic agent is 1-10 μm.

10. The method for preparing a composite insulator with cooling and embedded microcapsule hydrophobic agent according to claim 9, characterized in that: The mass ratio of the microcapsule hydrophobic agent to the umbrella cover substrate is 0.05-0.15:1.

Citation Information

Cited By

  • Nano-composite silicone rubber insulator with hydrophobic mobility and manufacturing method of nano-composite silicone rubber insulator

    CN120623791A

  • A nanocomposite silicone rubber insulator with hydrophobic migration and a manufacturing method thereof

    CN120623791B

  • Method for improving H-level insulating property of 10kV generator and application

    CN122371614A